Impact of the doctor-patient relationship on non-compliance with pharmacological medical prescription in chronic disease. A cross-sectional study - Ribeiro, Maria Isabel (2018)
In developed countries chronic disease is currently the main reason why people betake to health care [1]. Negative effects of non-compliance with medical prescription reduce the clinical benefits of the medication, leading in most cases to the use of unnecessary treatments, hospitalization and death [2]. Factors associated with non-compliance with medical prescription may be related to: the doctor-patient relationship, the treatment, the health system, the health condition and the socioeconomic situation. Objective/Aim: To assess the impact of the doctor-patient relationship on non compliance with pharmacological medical prescription in chronic disease. Methods: A cross-sectional design was developed based on a random sample of 141 patients with pathologies covered by Portuguese Exceptional Legislation. To collect the data, it was applied a questionnaire by interview between July 2017 and April 2018. The questionnaire included a list of non-compliance factors associated to doctor-patient relationship, developed by Cabral & Silva (2010) [3]. The IBM SPSS 24.0 software was used to analyse the data. Besides descriptive statistics, the data analysis involved the estimation of a logistic regression model, at a confidence level of 95%. Results: Chronic patients were aged between 20 and 95 years old, with a mean age of 65.3 years (SD = 19.39). Most were female (51.8%), married or lived in marital cohabitation (62.4%), retired (55.3%), and had up to the 3rd cycle of schooling (61%) and an income up to € 1,000 (62.4%). These patients suffered from Chronic Renal Insufficiency (CRI) (63.1%), Rheumatoid Arthritis (RA) and Psoriatic Arthritis (PA) (20.6%), Multiple Sclerosis (MS) (10.6%), Amyotrophic Lateral Sclerosis (ALS) (2.1%), Hepatitis C Virus (HCV) (2.1%), Hepatic disease (HD) (0.7%) and Gaucher Syndrome (GS) (0.7%). The active substances most dispensed were: ferrous sulphate (76.6%), folic acid (73.8%), calcium polysterenonosulfonate (53.2%), alfacalcidol (48.9%), epoetin β (43.3%), complex B (26.2%) for CRI; adalimumab (8.5%), etarnecept (7.1%) and Ustecinumab (4.3%) for RA and PA; interferon B (8.5%) for MS. Modal treatment time was 24 months. The main reason for non-compliance associated to doctor-patient relationship dimension was “the doctor prescribes too many medicines” (35%). The second most mentioned reason was “the fear to ask questions”(18.4%), followed by "I do not understand what doctors say" (17.5%) and the “lack of confidence in doctors” (6.8%). A patient who does not consider that “the doctor prescribes too many medications” has a lower risk of non-compliance with the therapeutic prescription [OR= 0.262; CI (95%): 0.112-0.617]. Conclusion: The doctor-patient relationship is fundamental for compliance with the prescribed therapy and consequently for the improvement of the clinical benefits of medication and well-being of the patient. References (Vancouver Style): [1]. Dowrick, C., Dixon-Woods, M., Holman, H., & Weinman, J. What is chronic illness? Chronic Illness, 1, 2005, 1-6. [2]. Bugalho A & Carneiro A. (2004). Intervenções para aumentar a adesão terapêutica em patologias crónicas. Lisboa Centro de Estudos de Medicina Baseada na Evidência - Faculdade de Medicina de Lisboa. [3]. Cabral, M., Silva, P. A adesão à terapêutica em Portugal: Atitudes e comportamentos da população portuguesa perante as prescrições médicas. APIFARMA, 2010.